Quantu features of two types of Dzyaloshinskii-Moriya coupling in antiferromagnetic spin chain - Zvyagin, A.A. (Физика низких температур, 1995)
A ID spin quantum system (S = 1/2) with the Dzyaloshinskii-Moriya interaction is studied. It is shown that this type of coupling in the antiferromagnetic chain with an odd structure with respect to the main axis accounts for a staggered magnetic ordering in the ground state. For an even structure the Dzyaloshinskii-Moriya interaction causes a helicoidal spin structure only. Correlation functions are calculated under different conditions.